Mémoire de fille - Ernaux, Annie (Gallimard, 2016)
« J'ai voulu l'oublier cette fille. L'oublier vraiment, c'est-à-dire ne plus avoir envie d'écrire sur elle. Ne plus penser que je dois écrire sur elle, son désir, sa folie, son idiotie et son orgueil, sa faim et son sang tari. Je n'y suis jamais parvenue. » Dans Mémoire de fille, Annie Ernaux replonge dans l'été 1958, celui de sa première nuit avec un homme, à la colonie de S dans l'Orne. Nuit dont l'onde de choc s'est propagée violemment dans son corps et sur son existence durant deux années. S'appuyant sur des images indélébiles de sa mémoire, des photos et des lettres écrites à ses amies, elle interroge cette fille qu'elle a été dans un va-et-vient implacable entre hier et aujourd'hui.
Section: 150 pages ; 21 cm
Keywords: 1900-1999; 1950-1959; approches et analyses; corps; cours; discipline; europe; france; lit301N; littérature; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sexualité; systèmes d'oppressions; thématiques; écriture des femmes*

Feminist avant-garde: art of the 1970s : the Sammlung Verbund Collection, Vienna - Schor, Gabriele; Galleria nazionale d'arte moderna (Italie); Círculo de Bellas Artes (Madrid, Espagne); Palais des beaux-arts (Bruxelles, Belgique); Mjellby konstmuseum; Hamburger Kunsthalle; Photographers' Gallery; Museum Moderner Kunst (Autriche); Sammlung Verbund.; Schor, Gabriele; Galleria nazionale d'arte moderna (Italie); Círculo de Bellas Artes (Madrid, Espagne); et al. (Prestel, 2016)
Featuring a wide variety of work from artists both well-known and under the radar, this dynamic book reveals how women artists reclaimed control of the feminine image in photography, video, and performance art. This book documents a tectonic change in the way women portray themselves in art. Historically, women were depicted as a projection of male fantasies, prejudices, and relationships. However in the 1970s, for the first time, female artists began collectively to investigate visual representations of their own selves. They studied their own bodies and created the prospect of determined feminine identities. Editor Gabriele Schor explores the Feminist Avant-Garde to emphasize the role that these artists played for the last four decades. The works are provocative, radical, poetic, ironic, angry, cynical and heartfelt. The artists shared a collective consciousness that reassessed, and even rejected, what came before, turning to new ways of expression in the fields of photography, performance, film, and video. The collection SAMMLUNG VERBUND founded in 2004 in Vienna focuses on the feminist art movement of the 1970s as one of the main areas and is with 500 works the largest collection with this emphasis. Included are works by Eleanor Antin, Cindy Sherman, Ana Mendieta, Nil Yalter, Ketty La Rocca, Birgit Jürgenssen, Renate Bertlmann, Francesca Woodman and others. This important book emphasizes the accomplishments of women artists who have made a name for themselves while encouraging the young generation.
Keywords: 1900-1999; 1970-1979; approches et analyses; arts; biographie; corps; cours; discipline; femmes* artistes; har4600; histoire de l'art; patriarcat; premier cycle; périodes historiques; sexisme; systèmes d'oppressions; thématiques